An Econometrics Study For The Impact Of Annual Growth Of Public Sector Spending And Unemployment Rate In Syria During The Period (1990-2020) - طويل, دانيا; شكيب بشماني (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The objective of this paper is to study the impact of public spending on unemployment rate in Syria during the period from 1990 to 2020. To this end , we used The Autoregressive Distributed Lag Models (ARDL). This study showed that there is a long-term equilibrium relationship between unemployment rate and the two indictors(growth of current and investment public sector spending). This means that divergence that can emerge in the short term can be corrected and returned to equilibrium in the long term. This study also showed in long term a scientific positive impact of growth of current public sector spending on the unemployment rate in Syria during the period studied, and unscientific negative impact of growth of investment public sector spending on the unemployment rate. while the study showed that in short term, there is a positive effect between the value of the unemployment rate and current public spending, and the presence of a scientific negative effect for the previous two values ​​of current public spending on the unemployment rate, and the absence of an effect for the value of the growth rate of public investment spending and the value of the unemployment rate, and the presence of a scientific negative effect for the second previous values ​​of public investment spending and Unemployment rate.